2012
DOI: 10.1007/s10585-012-9545-6
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 is critical for immunosuppression to promote cancer metastasis

Abstract: We previously found that cancer metastasis is accelerated by immunosuppression during Snail-induced epithelial-to-mesenchymal transition (EMT). However, the molecular mechanism still remained unclear. Here, we demonstrate that CCL2 is a critical determinant for both tumor metastasis and immunosuppression induced by Snail(+) tumor cells. CCL2 is significantly upregulated in various human tumor cells accompanied by Snail expression induced by snail transduction or TGFβ treatment. The Snail(+) tumor-derived CCL2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 40 publications
3
93
0
Order By: Relevance
“…CCL2 is one of the molecules involved in bone metastatic mechanism (5,6). Surely, CCL2 significantly increased in Snail þ tumor cells, and siRNA-ccl2 injection significantly suppressed Snail þ tumor growth and dissemination/metastasis as shown before (12). However, the siRNA-ccl2 injection hardly suppressed CD45…”
Section: Discussionmentioning
confidence: 94%
“…CCL2 is one of the molecules involved in bone metastatic mechanism (5,6). Surely, CCL2 significantly increased in Snail þ tumor cells, and siRNA-ccl2 injection significantly suppressed Snail þ tumor growth and dissemination/metastasis as shown before (12). However, the siRNA-ccl2 injection hardly suppressed CD45…”
Section: Discussionmentioning
confidence: 94%
“…However, their properties were mainly elucidated not from the tumor-mesenchymal interaction but their genetic back- , LGR5 + 32) , and CD44v6 + 33) . via production of CCL2 and subsequent induction of immunoregulatory dendritic cells (regDC) 38) . .…”
Section: E Tran Et Al Demonstrated the Neo-antigen Krasmentioning
confidence: 99%
“…On the basis of a unique strategy analyzing both tumor cells and host simultaneously, we previously demonstrated that Snail-induced EMT simultaneously causes tumor metastasis and immunosuppression in murine (13) and human system (34). However, the entire mechanism of cancer immunoevasion remains to be fully elucidated.…”
mentioning
confidence: 99%